Constraining Instantaneous Fluxes and Integrated Compositions of Fluvially Discharged Organic Matter. (11th August 2018) - Freymond, Chantal V.; Lupker, Maarten; Peterse, Francien; Haghipour, Negar; Wacker, Lukas; Filip, Florin; Giosan, Liviu; Eglinton, Timothy I.
Abstract: Fluvial export of organic carbon (OC) and burial in ocean sediments comprises an important carbon sink, but fluxes remain poorly constrained, particularly for specific organic components. Here OC and lipid biomarker contents and isotopic characteristics of suspended matter determined in depth profiles across an active channel close to the terminus of the Danube River are used to constrain instantaneous OC and biomarker fluxes and integrated compositions during high to moderate discharges. During high ( moderate ) discharge, the total Danube exports 8 ( 7 ) kg/s OC, 7 ( 3 ) g/s higher plant‐derived long‐chain fatty acids (LCFA), 34 ( 21 ) g/s short‐chain fatty acids (SCFA), and 0.5 ( 0.2 ) g/s soil bacterial membrane lipids (brGDGTs). Integrated stable carbon isotopic compositions were TOC: −28.0 ( −27.6 )‰, LCFA: −33.5 ( −32.8 )‰ and Δ 14 C TOC: −129 ( −38 )‰, LCFA: −134 ( −143 )‰, respectively. Such estimates will aid in establishing quantitative links between production, export, and burial of OC from the terrestrial biosphere. Key Points: Bulk organic carbon and biomarker concentrations as well as structural and isotopic composition were measured in depth profiles across a major river This data set, characterizing the suspended particulate matter, was combined with Acoustic Doppler Current Profiler water velocity data Cross‐section integrated suspended matter composition and instantaneous organic carbon and biomarker fluxes were calculated